Book Review: Richard Scragg New Zealand’s Legal System - Wright, Peter (Victoria University of Wellington Law Review, 2005)
This article is a book review of Richard Scragg New Zealand’s Legal System (Oxford University Press, Melbourne, 2005) (146 pages) NZ49.95. The book is a new guide to the principles of the legal system which introduces core legal concepts to law students. Even though the book does not have the depth and details of McDowell and Webb’s "The New Zealand Legal System", Wright recommends the book as an accessible study guide for law students in their first year.